Interactions between cell growth-regulating domains in the products of the adenovirus E1A oncogene. - Moran, B (1988)
Among the various biological activities expressed by the products of the adenovirus E1A gene are the abilities to induce cellular DNA synthesis and proliferation in quiescent primary baby rat kidney cells. The functional sites for these activities lie principally within two regions of the E1A proteins: an N-terminal region and a small second region of approximately 20 amino acids further downstream. To study the biological functions of the first domain, we constructed an in-frame deletion of amino acid positions 23 through 107 of the E1A products. This deletion did not impede the ability of the E1A products to transactivate the adenovirus early region 3 promoter in a transient-expression assay in HeLa cells. The ability to induce DNA synthesis in quiescent baby rat kidney cells was, however, lost in the absence of these sequences. Deletion of the small second region induced a form of S phase in which DNA synthesis occurred in the apparent absence of controls required for the cessation of DNA synthesis and progression through the remainder of the cell cycle. These cells did not appear to accumulate in or before G2, and many appeared to have a DNA content greater than that in G2. The functions of both domains are required for production of transformed foci in a ras cooperation assay. Focus formation occurred, however, even when the two domains were introduced on two separate plasmids. This complementation effect appeared to require expression of both of the mutant proteins and did not appear to result merely from recombination at the DNA level.